SECURITY AS PUBLIC INTEREST IN CONSTRUCTION LAW - Zwolak, Sławomir (Review of European and Comparative Law, 2018)
Polish construction law refers to the public interest in an indirect way, which consists primarily of value within a framework of security. The concept of security in construction law covers a range of issues and is a term quite wide. The special importance of safety results from its fundamental importance for society. The need to ensure security in the construction industry, leads to the need to balance the public interest and the individual. Respecting the public interest expressed in security, it is an essential prerequisite for restrictions on freedom of construction. In addition, in the context of general security, the article presents relevant solutions resulting from the German and English model.